Problematyka prywatności przy udzielaniu świadczeń zdrowotnych osobom starszym – wybrane aspekty prawne = Privacy issues in the provision of health services for the elderly – selected legal aspects - Wrześniewska-Wal, Iwona; Augustynowicz, Anna; Czerw, Aleksandra (Journal of Education, Health and Sport, 2015)
Wrześniewska-Wal Iwona, Augustynowicz Anna, Czerw Aleksandra. Problematyka prywatności przy udzielaniu świadczeń zdrowotnych osobom starszym – wybrane aspekty prawne = Privacy issues in the provision of health services for the elderly – selected legal aspects. Journal of Education, Health and Sport. 2015;5(6):281-290. ISSN 2391-8306. DOI 10.5281/zenodo.18600 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%286%29%3A281-290 https://pbn.nauka.gov.pl/works/566452 http://dx.doi.org/10.5281/zenodo.18600 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 – 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 21.04.2015. Revised 28.05.2015. Accepted: 14.06.2015. Problematyka prywatności przy udzielaniu świadczeń zdrowotnych osobom starszym – wybrane aspekty prawne Privacy issues in the provision of health services for the elderly – selected legal aspects Iwona Wrześniewska-Wal1, Anna Augustynowicz1, 2, Aleksandra Czerw2 1Zakład Ekonomiki, Prawa i Zarządzania, Szkoła Zdrowia Publicznego Centrum Medyczne Kształcenia Podyplomowego w Warszawie 2Zakład Zdrowia Publicznego Warszawskiego Uniwersytetu Medycznego Adres do korespondencji: Centrum Medyczne Kształcenia Podyplomowego 01 - 826 Warszawa; ul. Kleczewska 61/63; tel. 22 56-01-140 Streszczenie: O zawodzie lekarza można powiedzieć, że ma charakter humanistyczny, bo u jego podstaw leży życie i zdrowie człowieka, oraz respektowanie tej szczególnej wartości, jaką jest godność. Z godnością związane są wszelkie regulacje prawne, które chronią prywatność pacjentów. Są to przepisy odnoszące się do intymności, tajemnicy zawodowej oraz ochrony dokumentacji medycznej. Każdy pacjent ma prawo do poszanowania intymności i godności, w szczególności w czasie udzielania mu świadczeń zdrowotnych. Obowiązkiem lekarza jest troska by pozostały personel medyczny przestrzegał tych zasad. Intymność pacjenta, odnieść należy do wszelkich uczuć i działań nie tylko związanych z udzielaniem świadczeń zdrowotnych. Na tak pojmowaną intymność składa się dbanie o dobro pacjenta, szacunek dla pacjenta, zrozumienie jego sytuacji. Jednym z elementów tych praw jest również możliwość kontaktu pacjenta z innymi osobami, towarzyszenia osoby bliskiej przy udzielaniu świadczeń zdrowotnych oraz sprawowania przez tą osobę opieki nad pacjentem. Szczegóły dotyczące tych kontaktów określa regulamin szpitala bądź oddziału. Z prawem do prywatności łączą się gwarancje ochrony danych osobowych. Dane dotyczące stanu zdrowia pacjenta chronioną są w dwóch płaszczyznach. Chodzi tu o przepisy dotyczące prawa pacjenta do tajemnicy informacji z nim związanych oraz przepisy dotyczące ochrony dokumentacji medycznej. Tajemnica zawodowa obejmuje wszelkie informacje związane z pacjentem a uzyskane w związku z wykonywaniem zawodu medycznego. Przy czym obowiązek ten nie ma charakteru absolutnego albowiem ustawodawca enumeratywnie wskazał wyjątki w tym zakresie. Podmiot udzielający świadczeń zdrowotnych jest obowiązany prowadzić, przechowywać i udostępniać dokumentację medyczną pacjentowi i uprawnionym instytucjom oraz podmiotom w sposób określony w przepisach prawa, a także zapewnić ochronę danych zawartych w tej dokumentacji. Summary: The medical profession can say that is a humanist, because at its core the life and health of man and the respect of this particular value, which is dignity. With dignity are all related legal regulations that protect the privacy of patients. These include provisions relating to privacy, professional secrecy and the protection of medical records. Every patient has the right to respect for privacy and dignity, in particular at the time of granting him health benefits. The doctor is obliged concern that the remaining medical staff observe these principles. Intimacy patient should refer to all feelings and actions not only related to the provision of health services. On such notions of intimacy consists of caring for the patient’s welfare, respect for the patient’s understanding of his situation. One element of these rights is also possible to contact a patient with others, to accompany a close relative when granting health benefits and the exercise by that person of patient care. Details of these contacts defined in the regulations or the hospital ward. With the right to privacy join safeguards for the protection of personal data. Data on the health of the patient are protected in two planes. This includes provisions on the patient’s right to confidentiality of information associated with it and the provisions for the protection of medical records. Professional secrecy covers all information related to the patient and obtained in connection with the exercise of the medical profession. At the same time this obligation is not absolute because the legislature has exhaustively pointed to exceptions in this regard. The entity providing health services shall keep, store and share patient medical records and authorized institutions and entities in the manner specified in the law and ensure the protection of the data contained in this documentation. Słowa kluczowe: osoba starsza, prywatność, intymność, tajemnica zawodowa, dokumentacja medyczna. Key words: an older person, privacy, intimacy, professional secrecy, medical records.